INOVASI MODEL BISNIS BERKELANJUTAN DENGAN PENDEKATAN DESIGN THINKING: STUDI KASUS RITEL FESYEN KECIL ZAHRAZIZA.MFO - Halimah Fatimatus Zahra; Berto Mulia Wibawa (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
Zahraziza.mfo is a small Muslim fashion retailer in Surabaya that has experienced a decline in performance since 2023 despite its transition to digital sales channels. An internal business model analysis revealed misalignments between several Business Model Canvas elements namely customer segments, value proposition, channels, key activities, and key resources with post-pandemic changes in consumer behavior. This study aims to redesign Zahraziza.mfo’s business model to become more adaptive and sustainable through a Design Thinking approach. The research employs interviews, observations, and the five stages of Design Thinking, empathize, define, ideate, prototype, and test to explore customer needs and validate proposed solutions. The results are embodied in a sustainable business model prototype that focuses transformation on key leverage points of the model, specifically the value proposition, customer relationships, and channels. The prototype generates four strategic solution clusters: strengthening digital experience and trust, developing a sustainable capsule collection, implementing gradual circular economy initiatives, and refining brand identity. These solutions are designed to realign the firm’s value creation logic with customer needs and meanings. The redesigned business model is considered more aligned with internal capabilities, market expectations, and sustainability principles, thereby providing a design framework that is aligned with Zahraziza.mfo’s long-term competitiveness and performance goals. Keyword: Design Thinking, Business Model Innovation, Sustainable Business Model Innovation, Fashion Retail, Small Medium Enterprise.